2011
DOI: 10.1117/1.3616010
|View full text |Cite
|
Sign up to set email alerts
|

Multispectral and panchromatic image fusion based on improved bilateral filter

Abstract: Image fusion is of great importance to various remote sensing applications because many Earth observation satellites provide both high-resolution panchromatic (Pan) and lowresolution multispectral (MS) images. A number of fusion methods have been proposed, such as intensity-hue-saturation fusion and wavelet transform fusion methods. However, further studies are still necessary to improve the fusion performance for new types of remotely sensed images, such as IKONOS or QuickBird images. We propose an improved b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…The literature shows a large collection of pan-sharpening methods developed, [1][2][3][4][5][6][7] and recent reviews can be found in Refs. [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…The literature shows a large collection of pan-sharpening methods developed, [1][2][3][4][5][6][7] and recent reviews can be found in Refs. [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…11 Compared with traditional pixel-oriented method, object-oriented change detection (OOCD) method chooses geographic object as basic unit for change detection and provides a new solution to the mentioned difficulties. [17][18][19] Finally, the results of change detection are related with the scale; that is, a single scale is insufficient to capture all the characteristics of objects within different sizes, shapes, etc. 12,13 Scholars have proposed some effective OOCD methods; [14][15][16][17][18] e.g., Miller et al proposed a method to detect blobs changes between gray-scale images, that is, first using connectivity analysis to obtain objects and then finding the matching object of each object in another image to make a comparison.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the compressed sensing theory provides a new approach for computer vision [15–17], image acquisition [18, 19], and reconstruction [2022]. This method can get the reconstruction results as effectively as the traditional imaging systems do, or even higher quality (in resolution, SNR, etc.…”
Section: Introductionmentioning
confidence: 99%